DECONSTRUCTING MU’ASYARAH BI AL-MA’RUF: TOWARD A GENDER-JUST FRAMEWORK OF ISLAMIC FAMILY LAW - Anisa, Lina Nur (JURNAL HAKAM, 2025)
This research offers a novel contribution to Islamic family law by deconstructing the concept of mu’asyarah bil ma’ruf as a normative foundation for addressing contemporary legal and social challenges. Departing from traditional textual interpretations, the study reconceptualizes mu’asyarah bil ma’ruf as a dynamic and inclusive ethical-legal framework grounded in justice, reciprocity, and gender equality. The scope of the research covers ethical, social, and legal dimensions of harmonious family life in Islam, with particular attention to husband–wife relations and family justice. Employing qualitative library research, this study utilizes content and critical analysis of primary Islamic legal sources, court decisions, and relevant family law policies. The findings reveal that classical normative frameworks often reflect patriarchal assumptions that constrain women’s rights and fail to respond adequately to contemporary social dynamics, resulting in legal and social inequalities. Through a deconstructive approach, the research exposes these biases and proposes an alternative interpretation that emphasizes mutual respect, proportional rights and obligations, and substantive justice within the family. This study concludes that reinterpreting mu’asyarah bil ma’ruf is essential for developing a more just and responsive Islamic family law. Practically, the findings contribute to Islamic legal reform by providing a conceptual basis for gender-sensitive legislation, judicial interpretation, and family law policies that protect women and children while remaining firmly rooted in Islamic values.